2018
DOI: 10.1161/jaha.117.007568
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Emergency Medical Services Response Time and Bystander Intervention in Patients With Out‐of‐Hospital Cardiac Arrest

Abstract: BackgroundThe response time of emergency medical services (EMS) is an important determinant of survival after out‐of‐hospital cardiac arrest. We sought to identify upper limits of EMS response times and bystander interventions associated with neurologically intact survival.Methods and ResultsWe analyzed the records of 553 426 patients with out‐of‐hospital cardiac arrest in a Japanese registry between 2010 and 2014. The primary study end point was 1‐month neurologically intact survival (Cerebral Performance Cat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 43 publications
3
22
0
1
Order By: Relevance
“…Response time ≤ 7.5 min may lead to favorable neurological outcomes in OHCA patients [25]. Goto et al [26] reported that the upper limits of EMS response times associated with improved 1-month neurologically intact survival were 13 min when a witness started CPR and provided defibrillation, and 11 min CPR was initiated without defibrillation. On the other hand, Bürger et al [27] reported that rapid ambulance response is associated with a higher rate of survival from OHCA with good neurological outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Response time ≤ 7.5 min may lead to favorable neurological outcomes in OHCA patients [25]. Goto et al [26] reported that the upper limits of EMS response times associated with improved 1-month neurologically intact survival were 13 min when a witness started CPR and provided defibrillation, and 11 min CPR was initiated without defibrillation. On the other hand, Bürger et al [27] reported that rapid ambulance response is associated with a higher rate of survival from OHCA with good neurological outcome.…”
Section: Discussionmentioning
confidence: 99%
“…When applying the new TOR rule at 14 min of EMS-initiated CPR, the reduction in the patient transport rate to the ED is anticipated to be 10% (approximately 11,000 patients per year in Japan) ( Table 2). Reducing the number of transports for OHCA patients may help reduce the number of ambulances dispatched, shorten EMS response time, and ultimately improve survival in OHCA patients [33]. However, in Japan, EMS personnel cannot pronounce death on the scene for OHCA patients.…”
Section: Discussionmentioning
confidence: 99%
“…Ambulance response times have long been used as a surrogate measure of quality of prehospital care. [7] In many circumstances, including ST-segment elevation myocardial infarction [8] and out-of-hospital cardiac arrest, [9] lessening the time of arrival of ALS-trained personnel is benefi cial.…”
Section: Response Timesmentioning
confidence: 99%